Third International Congress on Epilepsy, Brain and Mind: Part 1 - Korczyn, Amos D; Schachter, Steven C; Amlerova, Jana; Bialer, Meir; van Emde Boas, Walter; Brázdil, Milan; Brodtkorb, Eylert; Engel, Jerome; Gotman, Jean; Komárek, Vladmir; Leppik, Ilo E; Marusic, Petr; et al. (Epilepsy & behavior, 2015)
Epilepsy is both a disease of the brain and the mind. Here, we present the first of two papers with extended summaries of selected presentations of the Third International Congress on Epilepsy, Brain and Mind (April 3-5, 2014; Brno, Czech Republic). Epilepsy in history and the arts and its relationships with religion were discussed, as were overviews of epilepsy and relevant aspects of social cognition, handedness, accelerated forgetting and autobiographical amnesia, and large-scale brain networks.
Keywords: Amnesia; Epilepsy; funkční lateralita; Music; Networks; Functional Laterality; metafyzické vztahy mezi duší a tělem; Internationality; lidé; kongresy jako téma; internacionalita; mozek; Religion; Social cognition; Congresses as Topic; epilepsie; Handedness; amnézie; Brain; Czech Republic; Mind-Body Relations, Metaphysical; Cognition; Česká republika; Accelerated forgetting; Social Behavior; sociální chování; Humans